Recurrent left atrial rhabdomyosarcoma: a case report - O. N. Antropova; T. V. Vishnyakova; I. V. Osipova (Российский кардиологический журнал)
Cardiac tumors are rare, and their diagnosis is a clinical problem associated with significant heterogeneity of pathology. The purpose of this publication is to report a rare known disease and analyze the problem for the purpose of medical education. In a case report, the following characteristic signs of a heart tumor were demonstrated: rapid progression of heart failure symptoms, systemic manifestations (anemia, severe weakness). The results of transthoracic and transesophageal echocardiography made it possible to interpret the intracardiac mass as a tumor recurrence. Histological examination confirmed the diagnosis of left atrial rhabdomyosarcoma. A specific of this case is the tumor recurrence 2 years after surgery.